Diseño Presupuestal Financiero para el Colegio Liceo Moderno Villa Luz - López Gaona, Diana Paola; Suárez Amado, María Carmenza (Universidad Antonio Nariño, 2023)
The private educational establishments that are supervised by the Ministry of National Education through the different territorial secretaries, have established in accordance with Law 115 of 1994, the criteria that define the tuition fees, pensions and periodic charges originated by virtue of the provision of the service; based on this the Liceo Moderno Villa Luz hereinafter LMV, has established the maximum value in which they can offer and develop the social object of the same.